Análisis del deficit presupuestal en funcionamiento de la Universidad Nacional de Colombia (2013)
This essay about the budget deficit in operating expenses of the National University of Colombia, firstly intends to find the root of financial problems of the entity. It researches the behavior of the revenue and expenditure in the University, as well as its composition and evolution in time. Secondly, it determines which have been the causes or situations that create the budget deficit in the institution. And finally, develops the main objective, which aims to respond to the need to search for alternative solutions that make sustainable the role of state, entrusted to the National University of Colombia.